Savitry Rambu Maudy Djunaidi - Djunaidi, Savitry R. Maudy; Amat, Anita Lidesna Shinta; Rini, Desi Indria; Dedy, Maria Agnes Etty (Universitas Nusa Cendana, 2023)
Background: Hyperuricemia is a condition where there is a metabolic disorders shown by increased of uric acid levels in the serum, such excessive amount of uric acid can manifest as gout. Soursop leaf (Annona muricata L.) contains active compounds that has the potential to reduce uric acid levels in rats. Research purposes: To determine the dose of ethanol extract of Soursop leaves that can reduce uric acid levels in rat’s blood. Method: This research was a true experimental, 24 white rats (Rattus novergicus) of Sprague Dawley were divided into 6 groups consisting of the normal control group without any treatment. the negative control group was induced by chicken liver juice, the positive control group was given allopurinol 18 mg /200gBB, and the 3 treatment groups that was given soursop extract with leveled dosage (10, 40 and 70 mg/200gBW) for 12 days. The difference between uric acid before and after the treatment of each group was done using One Way Annova, followed by Post hoc analysis. The changes in uric acid levels per day of observation, were analysis using Repeated Anova, followed by Post hoc analysis. Results: Ethanol extract of soursop leaves can reduce uric acid levels in the blood and is not significantly different from allopurinol (p>0.05). Doses of 10, 40 and 70 mg/200gBW had the same effect in reducing uric acid levels in rats, with the peak of decrease occurring on day 26, specificly 1.58 mg/dl (p<0.05) Conclusion: The ethanol extract of soursop leaves (Annona muricata L.) can reduce uric acid levels in rats. Doses of 10, 40 and 70 mg/200gBW had the same effectiveness as allopurinol in lowering the levels of uric acid in rats